Exploring the mechanisms of tetrahydrocurcumin in ameliorating nonalcoholic steatohepatitis based on network pharmacology and gut microbiota analysis in vivo and in vitro - Chen, Keyu; Wang, Jianbo; Luo, Shuang; Quan, Yunyun; Wei, Ping; Fu, Jiali; Ma, Jiali; Yang, Yuying; Liu, Yunten; Gao, Zhichong (Frontiers in Microbiology, 2025)
BackgroundThe prevalence of nonalcoholic steatohepatitis (NASH) is increasing every year, and there are very few approved therapeutic agents globally, making the search for potentially targeted therapeutic agents important.AimsTo investigate the anti-NASH effect of tetrahydrocurcumin (THC) and to further study the biological mechanism of THC anti-NASH from the perspective of intestinal flora.MethodsSeven-week-old female male C57BL/6J mice were randomly divided into two batches of six groups: (1) control group, (2) model group, (3) positive control group, (4) THC low-dose group, (5) THC medium-dose group, and (6) THC high-dose group. The first batch of mice were fed with high-fat chow for 16 weeks in the rest of the groups except the control group; and the second batch of mice were fed with MCS chow in the control group, and MCS chow in the rest of the groups. MCD feed for 4 weeks. Serum, feces and liver tissues were collected separately. In addition, NASH cell model was established by using free fatty acids to induce AML-12 cells. Network pharmacology, molecular docking, high-throughput sequencing, protein blotting, and real-time fluorescence quantitative PCR were used to investigate the mechanism of THC against NASH.ResultsThe intervention of THC improved the pathology of NASH, ameliorated liver injury, lowered lipid levels, and inhibited hepatic oxidative stress, inflammatory response and apoptosis compared with the high-fat feed-induced model group. In network pharmacology and animal experimental validation we found that THC reduced the expression of m RNA of PPARG, which may be the key to the improvement of NASH by THC. Intestinal flora analysis showed that THC altered the composition of the intestinal flora, which was characterized by a decrease in the proportion of Firmicutes/Bacteroidota.ConclusionThe results of this study suggest that THC exerts anti-NASH effects by improving lipid levels, decreasing oxidative stress, attenuating inflammatory responses, and increasing the anti-apoptotic capacity of liver cells, and its efficacy is importantly associated with decreasing the expression of PPARG and improving the intestinal flora. THC is expected to be a potential therapeutic agent for NASH.